A Case Report on Capecitabine Induced Hand Foot Syndrome and Mucositis - Prakasam, Ponni Jothi; Krishnan, Divya Gopala; Mohanta, Guru Prasad (Indian Journal of Pharmacy Practice)
Hand foot syndrome (HFS) is a dose-limiting toxicity of Capecitabine. Though HFS is not life threatening, it can affect the daily activities and quality of life of a patient. Proper patient education aids in early detection of HFS and in minimizing or preventing the harm caused by it. We report a case of an elderly male patient who received adjuvant chemotherapy with Capecitabine for advanced Gastric carcinoma. While on treatment, he developed signs and symptoms consistent with Capecitabine induced grade 2 HFS and oral mucositis. The adverse drug reaction causality assessment done using the WHO scale showed a ‘Probable’ association of the reaction with Capecitabine.
Keywords: Capecitabine; Gastric carcinoma; Hand foot syndrome; Mucositis; Patient education